Resurge deposits associated with the shallow marine early Cambrian Vakkejokk impact, north Sweden. (21st March 2019) - Ormö, J.; Minde, P.; Nielsen, A. T.; Alwmark, C.
Abstract: The lower Cambrian Vakkejokk Breccia is a proximal ejecta layer from a shallow marine impact. It is exposed for ~7 km along a steep mountainside in Lapland, northernmost Sweden. In its central parts, the layer is up to ~27 m thick. Here the breccia shows a vertical differentiation into (1) a lower subunit consisting of strongly deformed target sediments mixed with up to decameter size, mainly crystalline basement clasts (i.e., lower polymict breccia [LPB]); (2) a middle subunit consisting of a polymict, blocky to gravelly breccia, commonly graded (i.e., graded polymict breccia [GPB]), that, in turn, is sporadically overlain by (3) a few dm thick, sandy bed (i.e., top sandstone [TS]). Previous work interpreted the graded beds as deposited by resurging water during early crater modification. We made three short (<1.35 m) core drillings through the graded beds. The line‐logging technique previously used on cores from other marine‐target craters was complemented by logging of equal‐sized cells in photos made along the cores. Granulometry and clast lithology determinations provide further evidence for the top beds of the breccia being resurge deposits. However, the magnitude of this resurge can only be assessed by future deep core drilling of the infill of the crater hidden below the mountain.